1993
DOI: 10.1159/000267270
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Quick-Phase Intervals in Optokinetic Nystagmus

Abstract: The distribution of the intervals between quick phases in optokinetic nystagmus shows the same general characteristics as saccadic latency to visual targets and as congenital nystagmus. In each case, for intervals of 150 ms and above, the distribution of reciprocal latency is normal; at shorter intervals, there may be a second component equivalent to ‘express’ saccades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The start of a QP is determined by the saccadic trigger, which could be determined by SP duration (Anastasio, 1996;Carpenter, 1993Carpenter, , 1994, eye position (Chun & Robinson, 1978), or a combination of processes (Balaban & Ariel, 1992). Our results indicate that the threshold is dependent on both the SP start position and SP velocity and cannot be determined solely by position or duration.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The start of a QP is determined by the saccadic trigger, which could be determined by SP duration (Anastasio, 1996;Carpenter, 1993Carpenter, , 1994, eye position (Chun & Robinson, 1978), or a combination of processes (Balaban & Ariel, 1992). Our results indicate that the threshold is dependent on both the SP start position and SP velocity and cannot be determined solely by position or duration.…”
Section: Discussionmentioning
confidence: 72%
“…SPs are slow movements made in the direction of stimulus motion with a gain (SP speed ‚ stimulus speed) less than unity, which decreases with stimulus speed (Fletcher, Hain, & Zee, 1990) so complete retinal stabilization is seldom achieved. SPs tend to bring the eye position to a more central location, but the timing and amplitude of both SPs and QPs are highly variable (Anastasio, 1996;Balaban & Ariel, 1992;Carpenter, 1993Carpenter, , 1994Cheng & Outerbridge, 1974;Trillenberg, Zee, & Shelhamer, 2002). This variability is intrinsic and implies either an embedded stochastic process or complicated deterministic behavior manifesting as chaos.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our data did not allow us to determine when the programming of corrective saccades actually begins, we can still use the intersaccadic interval to compare the decision time of corrective saccades in the three different stimulus conditions assuming the programming begins at the same time. In addition, it has been demonstrated that the intersaccadic intervals of spontaneous saccades, such as in reading or optokinetic nystagmus (OKN), can be well described by the LATER model (Carpenter, 1993, Carpenter & McDonald, 2007). Interestingly, the latencies of corrective saccades in our experiments showed similar patterns of distribution to the intersaccadic intervals for those more “spontaneous”, reflexive saccades, with longer median latencies and more of the early latency saccades than those of visually-triggered saccade.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showing a degree of integration between saccades and the slow phases of OKN are consistent with previous research showing integration and similarities between saccades and the fast phases of OKN. Saccades and fast phases have a very similar main sequence (Guitton & Mandl, 1980) and latency distributions (Carpenter, 1993;Carpenter, 1994;Roos, Calandrini, & Carpenter, 2008) and can be modeled by accumulator models that were originally designed for saccades (Carpenter & Williams, 1995;Roos et al, 2008). Saccades and fast phases both suffer the saccadic inhibition effect produced by irrelevant visual stimuli, and interact to produce targeting saccades that are curved (Harrison et al, 2014).…”
Section: Okn Fast Phases and Saccadesmentioning
confidence: 99%